Analisis Faktor-faktor Stres Kerja Karyawan Studi Pada Bagian Umum & Personalia Perusahaan Daerah Air Minum (PDAM) Kota Pontianak - B11106089, Mustakim (Jurnal Manajemen Update, 2013)
This study will describe how employees work stress factors in the study on general affairs and personnel, where the research was conducted at the Municipal Waterworks (PDAM) Pontianak. The method used in this study using a survey through descriptive statistical method that is collecting data with questionnaires or question list given to employees of the general affairs and personnel to be filled. The population in this study were employees of the Municipal Waterworks (PDAM) Pontianak in General Affairs & Personnel which number 47 people. File was resulted from this questionnaire will be processed through descriptive data analysis. The results of this study found that the factors that cause employees work stress such as individual stressors (role conflict, workload, and career development), group stressors (work relationships and interpersonal demands), and organizational stressors (organizational structure and leadership). Based on the employees work stress factors study on general affairs and personnel Municipal Waterworks (PDAM) Pontianak can be said enough. Keywords: Employees Work Stress